Auctioning Incentive Contracts: An Experimental Study - Sander Onderstal; Arthur Van de Meerendonk (Tinbergen Institute, 2009)
In this note, we experimentally examine the relative performance of price-only auctions and multi-attribute auctions. We do so in procurement settings where the buyer can give the winning bidder incentives to exert effort on non-price dimensions after the auction. Both auctions theoretically implement the surplus maximizing mechanism. Our experiment confirms this result. Moreover, we observe that the “pie” is shared the same in both auctions between buyer and suppliers both in theory and in the lab (after accounting for learning effects).
Keywords: C91; D44; D86; 330; Procurement; Price-only auctions; Multi-attribute auctions; Incentive Contracts; Laboratory Experiment; Auktionstheorie; Anreizvertrag; Vertragstheorie; Test